Characterizations of cytokines and viral genomes in serum of patients with Dabie bandavirus infection - Dong, Zefeng; Yuan, Man; Xing, Yueping; Zhang, Hongkai; Shen, Qiang (Frontiers in Virology, 2025)
BackgroundTen cases with Dabie bandavirus infection were identified in Suzhou City, China, from April 2023 to August 2024. All 10 cases were hospitalized patients, and three died. We detected and analyzed the cytokine concentrations and viral genomes in the serum samples of these patients to identify the possible causes of the patients’ deaths and to analyze the viral genetic characteristics.MethodsBlood serum specimens were obtained from the 10 individuals with Dabie bandavirus infection in Suzhou City. The specific nucleic acid of Dabie bandavirus was detected using a real-time reverse transcription polymerase chain reaction assay (RT-qPCR). The cytokine concentrations in serum were detected by micro enzyme-linked immunosorbent assay (ELISA). The genomes of Dabie bandavirus were amplified using a designated primer pool. The DNA sequencing libraries were prepared using a ligation method. The sequencing process was performed using a Nanopore GridION X5 instrument. Phylogenetic trees for the L, M, and S segments of Dabie bandavirus were constructed using the maximum likelihood (ML) method in MEGA 11 software, with the bootstrap value set at 1,000.ResultsAll 10 patients with Dabie bandavirus infection exhibited a severe clinical course, resulting in three fatalities. The cytokine concentrations of CCL2, GM-CSF, IFN-γ, IL-1β, IL-6, IL-8, and TNF-α were significantly elevated in the fatal patients compared with the recovered cases; all p-values for these cytokine analyses were under 0.05. The Dabie bandavirus strains identified in Suzhou belonged to three distinct genotypes: A, B, and F. The nucleotide identities for the L, M, and S segments were 95.65%–99.76%, 93.73%–99.81%, and 94.62%–99.88%, respectively. The average evolutionary rate of segment S was higher than that of segment M and segment L. The ratio of dN/dS in the membrane protein was the highest. SZ03-TXF was a recombinant strain with the location of possible breakpoints at nucleotides 795 and 1,432 in the CDS region of the L segment.ConclusionA recombination event was identified in SZ03-TXF strain. High viral load and cytokine storm may be associated with the case fatality of Dabie bandavirus infection. We should strengthen the monitoring of nucleotide substitutions and conduct health education for high-risk populations so as to effectively prevent and control an epidemic of the Dabie bandavirus infection in the future.